2005
DOI: 10.1002/jcp.20319
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of five evolutionary conserved regions of the human tyrosine hydroxylase (TH) promoter: Implications for the engineering of a human TH minimal promoter assembled in a self‐inactivating lentiviral vector system

Abstract: A DNA fragment of about 13 kb containing the human tyrosine hydroxylase (TH) promoter was previously isolated from a genomic DNA library and sequenced. The 11 kb from the transcription start of the human TH promoter was successively joined to the green fluorescent protein (GFP) to generate a transgenic mouse model. High levels of GFP expression could be observed in TH-positive cells of the Substantia nigra of embryonic and adult mice. Intriguingly, the sequence of the human TH promoter showed a low degree of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(52 citation statements)
references
References 40 publications
(84 reference statements)
1
46
0
2
Order By: Relevance
“…Profile of gene expression and specificity for human TH-positive cells of the 6.3 kb minimal promoter and 1.2 kb fragment of the first intron of the human TH gene A previous study showed that a human TH minimal promoter driving GFP termed pGR382 (−194/+35) had a considerably high transcriptional activity in hNPCs, while it was silent in human skin carcinoma A431 cell line (Romano et al, 2005). However, this construct was not specific for TH-expressing differentiated hNPCs (Romano et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Profile of gene expression and specificity for human TH-positive cells of the 6.3 kb minimal promoter and 1.2 kb fragment of the first intron of the human TH gene A previous study showed that a human TH minimal promoter driving GFP termed pGR382 (−194/+35) had a considerably high transcriptional activity in hNPCs, while it was silent in human skin carcinoma A431 cell line (Romano et al, 2005). However, this construct was not specific for TH-expressing differentiated hNPCs (Romano et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…The degree of homology between the human and mouse TH promoters is about 46.6% (determined with a Clustalx program; Romano et al, 2005), whereas the human and rat TH promoters share only a 30% degree of homology (Gandelman et al, 1990;Kim et al, 2003b). The five CRs were placed upstream of the first-194 bp from the transcription start of the human TH promoter and the first 35 bp of the untranslated messenger RNA leader of the human TH gene (Romano et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations